(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
Due to the considerable increase in public expenditure with health issues, mainly regarding drugs, several countries, including Australia and England, have already implemented, or are in the process of discussing the adoption of measures to ensure the quality of health care provided to the population. One of the less harmful strategies, rarely used in Brazil, is the adoption of economic techniques applied to health, more specifically, pharmacoeconomic analysis. This paper aims to contribute to the dissemination of concepts and techniques of economic analysis with a view to incorporate these into policy decisions of expenditure rationalization and the search for clinical efficiency. It includes a literature review covering the types of costs and benefits in health issues, the methodologies of pharmacoeconomic analysis, cost-minimization, cost-benefits, cost-effectiveness and cost-utility analysis, as well as its main characteristics, advantages, disadvantages and applicability.